Face/façade: the visual and the ethical - Kalaga, Wojciech (Journal of Architecture and Urbanism, 2010)
Face and façade share not only the same etymological derivation, but also the appeal to the visual perceptual apparatus. Their operation as visual signs/texts, however, reaches far beyond the merely iconic; in the context of the Western culture, face and façade perform the role of the exterior as symbolically representing the interior. In spite of what they have in common, the two concepts connote different ethical values. Face, especially in the Levinasian sense, implies absolute sincerity and truthfulness; façade, as a “face of the building,” is in fact a simulacrum of the interior; it implies excess and uses performative-rhetorical devices of deception. Yet the metonimical representation of the inside by the façade naturalizes – through semiotic conventions and games – its fraudulently excessive character; it is only when façade – in its derivative sense as mask – returns to the face and becomes its metaphorical substitute, that its negative ethical value comes to the fore. The paper explores and theorizes – with intercultural references – the semiotic operation of face and façade, as well as provide analyses of visual examples.Veidas ir fasadas: vizualumo ir etiškumo aspektaiSantrauka. Pasitelkiant tarpkultūrinius pavyzdžius ir semantinės analizės metodą straipsnyje tiriami Veido ir Fasado vaizdinių/sąvokų reikšminis ir etinis aspektai. Ieškoma panašumo tarp abiejų vaizdinių/sąvokų etimologijos ir vizualinio suvokimo struktūrų. Gilinamasi į Veidą ir Fasadą kaip į eksterjero ženklus, simboliniame lygmenyje reprezentuojančius interjerą. Straipsnyje išryškinama, kad tiriamos sąvokos konotuoja skirtingas etines vertes nepaisant dalinio jų tarpusavio panašumo. Veidui priskiriama nuoširdumo ir tikrumo reikšmė. Fasadas (pastato veidas) interpretuojamas kaip interjero simuliakras, todėl siejamas su netikrumu, apgaulingumu.Reikšminiai žodžiai: veidas, fasadas, kaukė, metonimija, per- formatyvumas, retoriškumas.First Published Online: 22 May 2013